Effectiveness of magnesium sulfate compared to rocuronium for rapid sequence tracheal intubation in adults: clinical randomized trial - Barbosa,Fabiano Timbó (2020)
Abstract Introduction and objectives: Magnesium sulphate has been used in anesthesia because it has relevant clinical features such as: analgesia, autonomic response control and muscle relaxation. Using the agent to establish adequate conditions for tracheal intubation remains controversial. The aim of the study was to compare the effectiveness of magnesium sulfate and rocuronium for rapid sequence tracheal intubation in adults. Methods: Double blind, randomized, unicentric, prospective study assessed 68 patients, ASA 1 or 2, over 18 years, scheduled for appendectomy under general anesthesia. Patients were divided into two groups. GM patients received 50 mg.kg-1magnesium sulfate and GR patients, 1 mg.kg-1 rocuronium immediately before anesthesia induction. Arterial Blood Pressure (BP) and Heart Rate (HR) were measured in both groups at five times related to the administration of the drugs studied. The primary variable was the clinical status of tracheal intubation. Trial Registry: RBR-4xr92k. Results: GM was associated with no significant hemodynamic parameter change after injection. GM showed 85% (29/34) poor intubation clinical status, 15% (5/34) good, and 0% excellent (< 0.0001). Conclusion: Magnesium sulfate did not provide adequate clinical status when compared to rocuronium at a dose of 50 mg.kg-1 for rapid sequence intubation in adult patients.